2016
DOI: 10.1016/j.jval.2016.03.1018
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Postherpetic Neuralgia Reveals Widespread Use of Opioids, CNS Depressants, and Polypharmacy

Abstract: ConClusions: The number and percentage of ultra-orphan drugs approved by the FDA increased in comparison with orphan drugs for rare diseases with a larger number of patients in the period 1983-2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…12 Finally, a retrospective electronic health record analysis showed that 35% of patients treated for PHN received opioids; among patients who received opioids, 85% received them as first-line treatment. 13 Suaya et al showed that adult patients with diabetes mellitus who developed HZ more frequently received an opioid prescription versus controls. 14 Li et al showed that immunocompromised patients with HZ were more likely to have an opioid prescription versus controls without HZ.…”
Section: Introductionmentioning
confidence: 99%
“…12 Finally, a retrospective electronic health record analysis showed that 35% of patients treated for PHN received opioids; among patients who received opioids, 85% received them as first-line treatment. 13 Suaya et al showed that adult patients with diabetes mellitus who developed HZ more frequently received an opioid prescription versus controls. 14 Li et al showed that immunocompromised patients with HZ were more likely to have an opioid prescription versus controls without HZ.…”
Section: Introductionmentioning
confidence: 99%